Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1177/1354068813514884
|View full text |Cite
|
Sign up to set email alerts
|

Effects of party primaries on electoral performance

Abstract: One of the most relevant aspects of party democratization is the consequence of more inclusive methods of candidate selection, and particularly of primaries, for party competition. Despite its relevance, and contrary to the attention it has received in the US, the electoral consequences of primaries have rarely been analysed in Europe. This article assesses whether the use of one member one vote (OMOV) primaries for candidate selection affects the electoral result of the party and, if it does, in what directio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 29 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…Some political parties across the globe realising the importance of wide party membership have replaced closed primary elections with core or ordinary group member participation, thus One-Member-One-Vote (OMOV) to address the challenge of nepotism, cronyism, and political patronage. This approach solidifies internal party democratic politics (De Luca & Venturino, 2017;Ramiro, 2016).…”
Section: Background Of the Studymentioning
confidence: 86%
See 3 more Smart Citations
“…Some political parties across the globe realising the importance of wide party membership have replaced closed primary elections with core or ordinary group member participation, thus One-Member-One-Vote (OMOV) to address the challenge of nepotism, cronyism, and political patronage. This approach solidifies internal party democratic politics (De Luca & Venturino, 2017;Ramiro, 2016).…”
Section: Background Of the Studymentioning
confidence: 86%
“…According to Faucher (2015), political parties in United Kingdom (UK) and France have disposedoff constrictions relating to party membership with the use of primaries as engagement mechanisms with new members. According to Ramiro (2016), in his study of PSOE, a Socialist Spanish party; he indicated that an OMOV primary had a positive relationship on its electoral outcomes especially at the local level politics. Better electoral results were recorded by an average of 1.7 points of votes as a result of wide membership base.…”
Section: Background Of the Studymentioning
confidence: 99%
See 2 more Smart Citations